Women's involvement in BRAC development activities and child nutrition - Khatun, Masuma; Bhuiya, Abbas; Chowdhury, Mushtaque (BRAC Research and Evaluation Division (RED), 2019)
This study explores the effect of women's involvement in BRAC's income and health development activities on the nutritional status of their children aged 6-72 months. MUAC measurements of 1,518 children aged 6- 72 months (using TALC) were taken between April-August 1995 under the BRAC-lCDDR,B joint research project in Matlab using a four-cell-study design . Data analysis consisted of both bivariate and multivariate analysis, along with comparison with similar data from a baseline sun'ey done in 1992. Findings reveal that prevalence of severe PEM has decreased significantly from 23 .2% to 14.1% among children of BRAC member households (p<0.05) during the period between 1992 and 1995. However. among non-member households, the prevalence remained almost unchanged (21.2%). The positive effect of women's involvement in BRAC development activities on their child's nutritional status remained significant even after controlling for age and sex of the child; age. year of schooling and number of living children of the mother; per capita monthly expenditure; MCHFP area; and four study cells during regression procedure. The children, whose mothers were participating in BRAC development activities, were 41% less likely to suffer from severe malnutrition compared to those of non-member (p<0.05). However, gender differential in the prevalence of severe malnutrition was very pronounced among the children of BRAC member households (p<0.05). This may, in part. be explained by the fact that BRAC does not have gender focused component in its programme. Programmatic implications of these findings are discussed.